IOT Enabled Healthcare Monitoring System Utilizing MQTT Protocol - Hemanth Kumar N.; Asmita Poojari (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
IOT ENABLED HEALTHCARE MONITORING SYSTEM UTILIZING MQTT PROTOCOL utilizing the MQTT protocol offers a cost-effective and efficient solution for real-time health tracking. By integrating multiple sensors, including a heartbeat sensor, respiratory sensor, pulse oximeter, MEMS sensor, and the DHT11 temperature and humidity sensor, the system continuously monitors vital health parameters. The combination of NODE MCU and Arduino Mega ensures seamless data processing and transmission while leveraging the lightweight MQTT protocol for reliable, low-latency communication. This architecture minimizes power consumption and bandwidth usage, making it well-suited for continuous health monitoring applications. To further enhance its capabilities, the system incorporates GPS for real-time location tracking and GSM for remote communication, allowing healthcare providers to access patient data from anywhere. An LCD display provides local monitoring, enabling immediate access to critical information. This comprehensive setup ensures that healthcare professionals can respond promptly to emergencies while offering continuous monitoring, particularly in remote or critical care environments. By bridging the gap between patients and medical experts, this system significantly improves healthcare accessibility, efficiency, and response time, making it a valuable innovation in modern telemedicine and IoT-driven healthcare solutions.
Keywords: DHT11; Alert; MEMS Sensor; GPS; IOT